2011
DOI: 10.1112/jtopol/jtq038
|View full text |Cite
|
Sign up to set email alerts
|

Nilpotent groups without exactly polynomial Dehn function

Abstract: We prove super-quadratic lower bounds for the growth of the filling area function of a certain class of nilpotent Lie groups. This class contains groups for which it is known that their Dehn function grows no faster than n 2 log n. We therefore obtain the existence of (finitely generated) nilpotent groups whose Dehn functions do not have exactly polynomial growth and we thus answer a well-known question about the possible growth rate of Dehn functions of nilpotent groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Note that Theorem 2.28 does not give metric properties of asymptotic cones, only the topological property of being simply connected. In a simply connected asymptotic cone even of a nice nilpotent group, a Lipschitz loop does not necessarily bound a Lipschitz 2-disc or even an integral 2-current (it can be deduced from [6] for the Heisenberg group H 3 , for other examples see Wenger [235], and 3.2.C). But for groups with quadratic Dehn functions, the asymptotic cones are much nicer.…”
Section: Theorem 229mentioning
confidence: 98%
See 4 more Smart Citations
“…Note that Theorem 2.28 does not give metric properties of asymptotic cones, only the topological property of being simply connected. In a simply connected asymptotic cone even of a nice nilpotent group, a Lipschitz loop does not necessarily bound a Lipschitz 2-disc or even an integral 2-current (it can be deduced from [6] for the Heisenberg group H 3 , for other examples see Wenger [235], and 3.2.C). But for groups with quadratic Dehn functions, the asymptotic cones are much nicer.…”
Section: Theorem 229mentioning
confidence: 98%
“…Then we were not able to prove that the central square of G 10 has quadratic Dehn function (this example and the question can be found in [237,Section 5]). [235] showed that in fact central squares of nilpotent groups of class 2 often do not admit quadratic isoperimetric inequality. In particular, he proved Theorem 3.36 (Wenger [235]) The Dehn function of the central square of G 10 is strictly greater than quadratic.…”
Section: 2c Other Central Productsmentioning
confidence: 99%
See 3 more Smart Citations